Understanding the adoption of root, tuber and banana crops in sub-Saharan Africa. Project profile. - International Potato Center (International Potato Center, 2019)
Plant breeders can contribute a great deal to meeting farmer needs for new crop varieties that are well adapted to local climatic conditions and other stresses. But many additional factors will determine end-user choices and the level of uptake. This project seeks to develop a greater understanding of the key traits in root, tuber and banana crops that are preferred by farmers, traders, processors and consumers.